Analytical Solution for the Mass Transfer of Ozone of the Second Order from Gaseous Phase to Aqueous Phase - Yildirim, Ahmet; Ali Balci, Mehmet (Asian Journal of Chemistry, 2011)
In this work, we consider the problem of mass transfer of ozone of the second order from a gaseous phase into an aqueous phase by employing the homotopy perturbation method. The series solution of the governing system of differential equations is obtained. Some examples have been included. The effects of the temperature and hydroxyl ion reaction order to the solutions are illustrated by some plots.